The effect of a single session of moderate and heavy intensity weight-lifting exercise on plasma testosterone and cortisol in elite male weight-lifters - Rahimi, A.; Tayebi, S. M. (Annals of Applied Sport Science, 2013)
The aim of this study was effect of a single session of weight-lifting exercise on serum testosterone and cortisol and testosterone-cortisol ratio changes in elite weight-lifter of Mazandaran state. 10 elite weight-lifter of Mazandaran state was selected randomly. Moderate-intensity exercise was contained stand snatch (2 sets with 3 repeats of 60 one repeat maximum), Olympic snatch (2 sets with 2 repeats of 60 1RM and 1 sets with 2 repeats of 70 1RM), Olympic clean & jerk (2 sets with 2 repeats of 60 1RM and 1 sets with 2 repeats of 70 1RM), squat on chest (2 sets with 3 repeats of 70 1RM); and heavy-intensity exercise was contained Olympic snatch (idoneous warm up and reach to %100 of record), Olympic clean & jerk (idoneous warm up and reach to %100 of record), mean lift (2 sets with 3 repeat of %120 Olympic snatch record), squat on chest (idoneous warm up and reach to %100 of record). Blood samples were taken at 30 minutes previous and immediately post exercise while the subjects were overnight fast (at least 12h). Blood variables were measurement containing Hemoglobin, heamatocrit, Testosterone and cortisol. Data were analyzed by spss program and paired sample t-test was used to compare mean of previous and Post of information. Finally any significant changes were not observed in blood variables not only in moderate-intensity exercise but also in heavy-intensity exercise. Insignificant changes in testosterone, cortisol and testosterone-cortisol ratio may be accounted as exercise performance time and fitness level of weightlifters.